Legitimacy intermediation in the multilevel European polity and its collapse in the euro crisis - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2012)
This essay re-examines the dual - republican and liberal - foundations of democratic legitimacy in the Western traditions of normative political theory. Considered in isolation, the European Union conforms to liberal standards but cannot satisfy republican criteria. Given these conflicting standards, debates on the alleged European democratic deficit have remained inconclusive. Moreover, they have failed to pay sufficient attention to the multilevel character of the European polity and to the normative potential of legitimacy intermediation in its two-step compliance and legitimating relationships. I argue, however, that the capacity of democratic member states to legitimate the exercise of European governing functions is being destroyed in the present euro crisis, and I briefly discuss the implications of this new constellation. – – In der westlichen Tradition der normativen politischen Theorie beruht demokratische Legitimität auf der doppelten Grundlage republikanischer und liberaler Prinzipien. Für sich betrachtet entspricht die Europäische Union zwar liberalen Kriterien, aber eben nicht den republikanischen Anforderungen. Angesichts so unterschiedlicher Kriterien konnte es auch im Streit über das angebliche europäische Demokratiedefizit keine Einigung geben. Überdies ignorierte diese Diskussion den Mehrebenen-Charakter der europäischen Politik und das normative Potenzial der Legitimationsvermittlung zwischen Union und Bürgern durch die demokratisch verfassten Mitgliedstaaten. Die gegenwärtige Eurokrise allerdings zerstört die Fähigkeit demokratischer Mitgliedstaaten, die Ausübung europäischer Herrschaftsfunktionen zu legitimieren. Der Aufsatz erörtert die Implikationen dieser neuen Konstellation.
Keywords: 300; Öffentliche Schulden; EU-Politik; Demokratie; Legitimität; Eurozone